2020
DOI: 10.3389/fnut.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Terfezia boudieri: A Desert Truffle With Anticancer and Immunomodulatory Activities

Abstract: Desert truffles have high nutritional value and grow wild in the Mediterranean basin and Western Asia. Although, many studies were performed to evaluate truffles nutritious values and phytochemical composition, studies are limited to evaluate their anticancer and/ or immunomodulatory effects. Our study was conducted to evaluate the anticancer and immunomodulatory effects of Terfezia boudieri (desert truffle). Different solvent extracts were prepared from the truffle and MTT assay was used to measure their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…Human immune system is composed of sophisticated network of cells and organs that work together to provide protection against different pathogens [ 28 ]. In our study, we evaluated the change in the function of innate and acquired immune response after treatment with different extract and fractions from H. orientalis L. In the lymphocyte proliferation assay, the highest response was observed in n -hexane fraction followed by hydroalcoholic extract.…”
Section: Discussionmentioning
confidence: 99%
“…Human immune system is composed of sophisticated network of cells and organs that work together to provide protection against different pathogens [ 28 ]. In our study, we evaluated the change in the function of innate and acquired immune response after treatment with different extract and fractions from H. orientalis L. In the lymphocyte proliferation assay, the highest response was observed in n -hexane fraction followed by hydroalcoholic extract.…”
Section: Discussionmentioning
confidence: 99%
“…Спленоциты получали из селезенки животных по методу, описанному ранее [10,11]. Для этого селезенку удаляли, паренхиму осторожно отделяли от капсулы, фрагментировали, фильтровали через клеточный фильтр с размерами пор 100 мкм.…”
Section: материал и методыunclassified
“…This fungal species is highly appreciated by several populations due to its high nutritional value (Bouzadi et al 2017;Vahdani et al 2017;Akyüz and Kirbag 2018) and its excellent medicinal properties. Several studies have demonstrated these therapeutic vertues, such as antimicrobial activity (Neggaz and Fortas 2013;Schillaci et al 2017;Malik et al 2018;Harir et al 2019), anticarcinogenic activity (Attia et al 2018;Dahham et al 2018;Al Obaydi et al 2020), and antioxidant activity (Al-Laith 2010; Dogan and Aydin 2013;Gouzi et al 2013;Hamza et al 2016;Neggaz et al 2018).…”
Section: Introductionmentioning
confidence: 99%